Handbook of electrical heating for industry - Erickson, C. J. (C. James) (Institute of electrical and electronics engineers, 1995)
"This practical guide gives excellent hands-on advice to engineers who do not have a wide knowledge of the field of electrical heating. Drawing on a wide variety of sources and over thirty-seven years of experience, C. J. Erickson provides tips and suggestions on how to specify, install, and operate electrical heating systems for a broad range of industrial applications. Numerous examples are given for calculations and model specifications, and practical instructions are also included." "This book will give you the tools you need to apply many of the methods suitable for use in industry." "Key features you'll put to immediate use include detailed instructions on selection, specification, installation, and operation of electrical heating and controls; invaluable samples of specifications for many types of heating systems; comprehensive material on heat transfer to develop your own power requirements; empirical formulas for designing induction heating systems - that have never been published before!; numerous heating methods and their applications to help you choose the best method for your own situation; in-depth coverage of electrical pipe heating, heating control specifications and philosophy, factory and field check-out instructions, and more!" "This book will be of particular interest to electrical, process, industrial, and maintenance engineers and electricians who want practical, hands-on advice and do not have time to wade through a lot of theory."--BOOK JACKET.